Teacher Discourse in Postdigital Education: A Critical and Systematic Literature Review - Feriyansyah, Feriyansyah; Murtiningsih, Siti; Nugroho, Hastanti Widy (Newinera Publisher, 2025)
This study reviews research trends on teacher discourse in postdigital education by examining 26 Scopus-indexed publications from 2019 to 2024 retrieved using the keywords “postdigital education” and “teacher.” Findings reveal limited scholarly attention, with the Postdigital Science and Education journal leading in publication volume. A cluster analysis uncovered ten thematic groupings higher education, digital citizenship, professional digital competence, critical pedagogy, teacher education, COVID-19 responses, and datafication, among others. Seminal contributions include Rapanta et al. (2020) on teacher presence in online instruction; Hrastinski et al. (2019) on educators’ critical imaginaries amid AI and robotics; Green et al. (2020) on transition design for remote learning; Fawns et al. (2021) on ecological datafication frameworks; and Örtegren (2022) on digital competence for citizenship. By synthesizing these insights, the study reconceptualizes teachers as relational, ethical, dialogical, critical, and transformative “subjects-in-becoming” who actively shape learning environments, counteract algorithmic reduction, and foster democratic empowerment. It argues that future teacher-governance models must embrace socio-technical complexity through enhanced digital competence, locally grounded postdigital identities, critical pedagogy and curriculum co-creation, ecological data practices, and flexible, dialogical pedagogies aligned with digital-citizenship ethics. These insights inform future research and policy directions in education.